End of the line - Russell, Jay; Wohlbruck, John; Allen, Lewis (La Crosse, Wisconsin Platinum Disc Corp., 2003)
In the name of the progress, a railroad company takes a magnificent step backward when management decides to abandon the rails for the air freight. Now two lifelong Southern Railroad workers are suddenly unemployed and their town is going out of business. Rather than sit back as their lives and careers are destroyed, the duo-two of the screen's most unlikely heroes-take off for the company's Chicago corporate headquarters in a stolen locomotive to tell the chairman of the board a thing or two and fight for their livelihoods and their own town.
Co-producer, Walker Stuart ; Executive producer, Mary Steenburgen.
Wilford Brimley, Kevin Bacon, Mary Steenburgen, Levon Helm.
Dolby digital.
In English.